2020
DOI: 10.1111/ppa.13136
|View full text |Cite
|
Sign up to set email alerts
|

Bidirectional colonization and biofilm formation by Erwinia psidii in eucalypt plants

Abstract: Dieback and wilt caused by Erwinia psidii is an emerging disease that has been causing considerable damage in eucalypt plantations. Because it is a recently emerged disease, several aspects of the bacterial interaction with its host still remain to be elucidated. In this work, we studied the E. psidii colonization and biofilm formation in eucalypt tissues by specific detection using PCR and scanning electron microscopy (SEM). The results indicate that the bacterium is able to translocate in stem tissue mainly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 44 publications
1
1
0
Order By: Relevance
“…As was demonstrated histologically in a previous work for Erwinia psidii in eucalypt (Caires et al, 2020), our work showed that R . solanacearum translocates acropetally and basipetally in both susceptible and resistant eucalypt clones.…”
Section: Discussionsupporting
confidence: 89%
“…As was demonstrated histologically in a previous work for Erwinia psidii in eucalypt (Caires et al, 2020), our work showed that R . solanacearum translocates acropetally and basipetally in both susceptible and resistant eucalypt clones.…”
Section: Discussionsupporting
confidence: 89%
“…Production losses can reach 30% in forests planted with susceptible genotypes. The disease is caused by the plant-pathogenic bacterium Erwinia psidii (RODRIGUES NETO et al, 1983), which colonizes the xylem vessels and parenchymal intercellular spaces (CHAI et al, 2017;CAIRES et al, 2020). Besides affecting eucalyptus, the pathogen can cause serious damage to guava and papaya crops in tropical and subtropical conditions (RODRIGUES NETO et al, 1983;COUTINHO et al, 2011;CHAI et al, 2017).…”
Section: Introductionmentioning
confidence: 99%